Novel Glycerol-Crosslinked Poly(acrylic acid) Hydrogel for Encapsulation and Release of Benzocaine - Lee, Angela Lisandra S (Archīum Ateneo, 2011)
Drug delivery by a controlled-release mechanism offers several advantages over traditional delivery systems such as improved therapeutic activity, reduced number of drug administrations, as well as minimizing the risk of over-dose or under-dose. In this study, attempt has been made to develop a novel controlled release device from glycerol crosslinked poly(acrylic acid) hydrogels. Glycerol crosslinked poly(acrylic acid) was fabricated by polymerizing acrylic acid and crosslinking the polymer with glycerol in the same reaction pot in the presence of benzoyl peroxide and Novozym 435. The fabricated hydrogel swelled more than 100% in neutral, acidic and basic buffer solutions. Swelling was pH and temperature dependent. The hydrogel encapsulated the drug benzocaine; the amount encapsulated was dependent on time, temperature and initial benzocaine concentration. The hydrogel also released the drug at a controlled rate.